Financial education and access to savings accounts: Complements or substitutes? Evidence from Ugandan youth clubs - Dean Karlan; Julian Jamison; Jonathan Zinman (Yale University, Economic Growth Center, 2014)
Evidence on the effectiveness of financial education and formal savings account access is lacking, particularly for youth. We randomly assign 250 youth clubs to receive either financial education, access to a cheap group account, or both. The financial education treatments increase financial literacy; the account-only treatment does not. Administrative data shows the education plus account treatment increases bank savings relative to account-only. But survey-measured total savings shows roughly equal increases across all treatment arms. Earned income also increases in all treatment arms. We find little evidence that education and account access are strong complements, and some evidence they are substitutes.
Keywords: D12; D91; O12; 330; financial education; financial literacy; financial access; savings; youth savings; microsaving